Path dependence - Claudius Gräbner-Radkowitsch; Jakob Kapeller (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2024)
This short paper explains the theory of path dependence and clarifies its relation to concepts such as positive feedback or lock-in, arguing that path dependence is a core theoretical element of political economy in general, and institutional and evolutionary economics in particular. We first clarify the core conceptual elements of path dependence, show how it is relevant in a wide variety of problems and approaches, and situate these diverse applications in a common theoretical understanding that can be synthesized as a general mechanism. We then discuss the different ways in which path dependence has been theorized in evolutionary-institutional economics and related schools of thought. Finally, we present some archetypical models of path dependent processes.
Keywords: B15; B25; B52; B55; C69; 330; Pfadabhängigkeit; Theorie; Modellierung